2020
DOI: 10.7554/elife.53986
|View full text |Cite
|
Sign up to set email alerts
|

Slo2 potassium channel function depends on RNA editing-regulated expression of a SCYL1 protein

Abstract: Slo2 potassium channels play important roles in neuronal function, and their mutations in humans may cause epilepsies and cognitive defects. However, it is largely unknown how Slo2 is regulated by other proteins. Here we show that the function of C. elegans Slo2 (SLO-2) depends on adr-1, a gene important to RNA editing. ADR-1 promotes SLO-2 function not by editing the transcripts of slo-2 but those of scyl-1, which encodes an orthologue of mammalian SCYL1. Transcripts of scyl-1 are greatly decreased in adr-1 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The functional consequences of editing within coding regions are poorly studied in C. elegans. A recent study reported ADAR-mediated regulation of SLO-2 activity in C. elegans neurons, but no editing of slo-2 transcripts was observed from RNA isolated from whole animals (Niu et al 2020). We identified editing within the slo-2 coding sequence in adult neural cells.…”
Section: Discussionmentioning
confidence: 59%
“…The functional consequences of editing within coding regions are poorly studied in C. elegans. A recent study reported ADAR-mediated regulation of SLO-2 activity in C. elegans neurons, but no editing of slo-2 transcripts was observed from RNA isolated from whole animals (Niu et al 2020). We identified editing within the slo-2 coding sequence in adult neural cells.…”
Section: Discussionmentioning
confidence: 59%
“…The neuron models presented in this work rely on experimental data available in literature [29,30,32,40]. All the reference experimental recordings have been recorded from immobilized worms in the whole-cell configuration, using both voltage-and current-clamp protocols.…”
Section: Elegans Neurons Electrophysiology and Experimental Datamentioning
confidence: 99%
“…In this paper, we model the electrical dynamics at the single neuron level of three interneurons, AVA, AIY, and RIM (which also acts as motor neuron), and three motor neurons, VA5, VB6, and VD5. The choice of the neurons is based on the availability of high-quality electrophysiology data [29,30,32,39,40] and the interesting variety of whole-cell dynamics exhibited by each of the selected neurons. These dynamics are not only interesting from a theoretical point of view, but also have important implications for understanding the functional role of these interneurons and motor neurons in neural circuits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fragile X mental retardation protein (FMRP) increases the P o of K Na 1.1 [75], and TMEM16C directly interacts with K Na 1.1 subunits to increase their Na + sensitivity and increase channel activity [76]. SCYL1 has also been found to increase the P o of K Na 1.1 when the two proteins are coexpressed in Xenopus oocytes, and their overlapping expression patterns in mouse brain regions suggest that this binding protein may regulate K Na 1.1 activity in neurons [77]. Preventing the physical or functional interaction with these proteins may suppress hyperactive K Na 1.1 channel activity.…”
Section: Potential New Inhibitor Modalitiesmentioning
confidence: 99%